Re-living Zimbabwe’s liberation struggle (Second Chimurenga) through selected songs of Simon Chimbetu, in oral history: heritage and identity - Peterson, Dewah; Tembo, Charles (Research Institute for Theology and Religion, 2016)
Reliving Zimbabwe’s liberation struggle (Second Chimurenga) through Simon Chimbetu’s selected songs